2014
DOI: 10.1186/s13046-014-0107-4
|View full text |Cite
|
Sign up to set email alerts
|

Wnt3a expression is associated with epithelial-mesenchymal transition and promotes colon cancer progression

Abstract: IntroductionEpithelial–mesenchymal transition (EMT) contributes to the progression and metastasis of cancer cells and is associated with a more invasive phenotype of cancer. The Wnt/β-catenin signaling pathway is one of the major pathways involved in EMT regulation. Many studies provide evidence that β-catenin, the key regulator of the canonical Wnt signaling pathway, is important in regulating EMT in cancer. However, the roles of Wnt3a, the representative canonical Wnt ligand, in EMT and colon cancer progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 42 publications
3
67
1
Order By: Relevance
“…In fact, metastasis was deemed as an essential factor to estimate clinical stages, and it was also prone to occur in less-differentiated malignancies. This result is consistent with those of previous studies investigating colorectal cancer [20,34], hepatocellular carcinoma [25,26], lung cancer [21], and melanoma [28], in which overexpression of Wnt3a could significantly enhance the invasion and migration potential of tumor cells by inducing epithelial-to-mesenchymal transition (EMT) and the metastasis-related protein matrix metalloproteinases (MMP)-2, -7, and -9. In addition, Wnt3a has been reported to be involved in the induction of CSC characteristics both in vitro and in vivo [16,35].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, metastasis was deemed as an essential factor to estimate clinical stages, and it was also prone to occur in less-differentiated malignancies. This result is consistent with those of previous studies investigating colorectal cancer [20,34], hepatocellular carcinoma [25,26], lung cancer [21], and melanoma [28], in which overexpression of Wnt3a could significantly enhance the invasion and migration potential of tumor cells by inducing epithelial-to-mesenchymal transition (EMT) and the metastasis-related protein matrix metalloproteinases (MMP)-2, -7, and -9. In addition, Wnt3a has been reported to be involved in the induction of CSC characteristics both in vitro and in vivo [16,35].…”
Section: Discussionsupporting
confidence: 92%
“…As previously reported, the aberrant expression of Wnt3a was also found in several human malignancies, including glioblastoma [16,17], mammary adenocarcinoma [18,19], colon carcinoma [20], lung cancer [21], prostate cancer [22], malignant mesothelioma [23], esophageal squamous cell carcinoma [24], hepatocellular carcinoma [25][26][27], and melanoma [28]. In these malignant tumors, Wnt3a expression is closely related to tumor growth, metastasis, chemo-/ radio-resistance and maintenance of CSC characteristics.…”
Section: Discussionsupporting
confidence: 64%
“…83 Similarly, wnt3a has been associated with the progression of a variety of tumors. 84 On the contrary, wnt3a and wnt5a influence on chondrocytes presents a more apparent effect. Chondrocytes resemble NP cells, as both reside in avascular tissues of which the function is to distribute and transfer biomechanical pressure, 85 appointing chondrocytes as a potential alternative to NP cells.…”
Section: Wnt3a and Wnt5a As Tools For Regeneration Of The Intervertebmentioning
confidence: 99%
“…CRC metastasis could be also promoted by inducing EMT through a β-catenin-dependent pathway [72]. Another study by Qi et al [73] demonstrated that Wnt3a overexpression leads to the distribution of cytosolic β-catenin, downregulation of epithelial markers, and overexpression of mesenchymal markers, in both cellular and animal models of colorectal cancer. Collectively, Wnt/β-catenin signaling may modulate the chemosensitivity of CRC through EMT.…”
Section: Wnt/β-catenin Signaling and Colorectal Cancer Epithelial-mesmentioning
confidence: 99%